Keberkesanan cerpen dalam mempertingkatkan prestasi penulisan karangan Bahasa Melayu dalam kalangan murid - Jamian, Abdul Rasid; Othman, Shamsudin; Md Yusof, Norzila (Dewan Bahasa dan Pustaka, 2013)
This research analyses the effectiveness of literature texts to upgrade the performance of 64 average-achiever students in Form Two. This experimental research was conducted to compare the effectiveness of the use of literature texts and conventional methods of teaching composition. Both groups were given two tests, namely pre-test and post-test to compare the performance of the overall composition, elaboration of points and sentence type. The research findings of the pre-test and post-test show that the teaching of composition using the literature texts is more effective than the conventional method.